TiB2 / TiC reinforced high-silicon heat-resistant aluminum-based composite material and preparation method thereof
Through the two -stage reaction method, the TIB2/TIC enhanced phase is generated in the original place in the aluminum base, which solves the problem of weak combination of ceramic particles and metal base interfaces, and realizes the improvement of material mechanical properties and simplified the process of preparation. It is suitable for high -efficiency and mass production.
Patent Information
- Application Number
- CN202411537130.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-28
AI Technical Summary
The preparation process of existing ceramic particle-reinforced aluminum-based composite materials is complicated, the interface bond between the ceramic particles and the metal-based composite is weak, the reaction rate is low, and the particles are agglomerated and not dispersed, making it difficult to achieve efficient mass production.
Adopting two stages of reaction method, TIB2/TIC enhanced phase is generated in the original place in the aluminum base. The small ball is prepared through high -energy ball grinding and centrifugal spray. Based on boron oxide and metal oxides to promote the production and decentralization of ceramic particles, and through electromagnetic, machinery, and The method of alternating ultrasonic stirring circulation to ensure a good combination of ceramic particles and metal base interfaces.
It improves the mechanical properties of materials, enhances the decentralization of ceramic particles, reduces preparation costs, achieves high -efficiency large -scale production, and does not produce harmful gases, which is harmless to the environment.
Smart Images

Figure CN119372519A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal-based composite materials, and in particular relates to a TiB2 / TiC reinforced high-silicon heat-resistant aluminum-based composite material and a preparation method thereof. Background Art
[0002] Aerospace equipment such as deep space probes, advanced fighters and hypersonic vehicles are currently developing in the direction of long flight time, high load and high maneuverability, which has put forward an urgent demand for lightweight and high-strength materials. Composite materials refer to new materials that are compounded in different ways by metals, polymers, inorganic non-materials and other types of materials. The components complement each other and are interrelated and synergistic, and have incomparable advantages over single materials. Applying advanced composite materials with excellent mechanical properties to the aerospace field can achieve a significant reduction in equipment weight, increase payload and reduce energy consumption.
[0003] Particle-reinforced metal matrix composites are one of the most promising advanced materials in the 21st century. They have high specific strength, high specific stiffness, high specific modulus, and good high temperature performance. They are also wear-resistant, fatigue-resistant, have low thermal expansion coefficients, and good thermal conductivity. Particle-reinforced aluminum matrix composites are highly valued for their simple production process, low cost, and isotropic materials. They can adjust the performance of composites by changing the size, volume fraction, and heat treatment process of the reinforcing particles. They have broad application prospects in the field of aerospace materials.
[0004] In recent years, there are more and more methods for preparing micro-nano ceramic-metal matrix composite materials, but most of them are single-phase or dual-phase ceramic particle reinforcement, and it is difficult to evenly disperse ceramic particles in the aluminum matrix. Chinese patent application CN116607041A provides an in-situ dual-phase nanoparticle reinforced aluminum matrix composite material and its preparation method, which generates in-situ (ZrB2+Al2O3) particles by a molten salt method, and uses argon to add the reaction salt to the melt. The experimental process is relatively complicated and has great harm to the environment. Chinese patent CN116144997B provides a high-performance aluminum matrix composite material and its preparation method, which adds TiO2 nanoparticles to a semi-solid slurry prepared from a matrix aluminum alloy, and performs hot forging + cold forging on the composite material. The process of this method is very cumbersome, and the interface bonding problem between the added particles and the matrix is more prominent. Chinese patent CN115418520A provides a method for preparing an in-situ Al2O3 particle-reinforced aluminum-based composite material, which comprises mixing the raw materials and adding them into a vortex metal liquid, and then taking the semi-solid slurry and performing reciprocating impact. This method cannot disperse the nano-scale particle agglomeration, and the method is relatively dangerous and difficult to operate.
[0005] Most previous inventions of ceramic particle reinforced aluminum-based composite materials have problems such as complicated and time-consuming processes, weak interface bonding between ceramic particles and metal matrix, low reaction rate, and particle agglomeration and non-dispersion. It is urgent to explore a method for preparing metal-based composite materials that can improve the mechanical properties of metal-based composite materials, is simple to operate, and can be produced on a large scale. Summary of the invention
[0006] In view of the above-mentioned shortcomings of the prior art, the present invention provides a TiB2 / TiC reinforced high-silicon heat-resistant aluminum-based composite material and a preparation method thereof.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] A method for preparing a TiB2 / TiC reinforced high-silicon heat-resistant aluminum-based composite material comprises the following steps:
[0009] (1) Aluminum powder, titanium powder and metal oxide or metal powder are mixed by high-energy ball milling, and the mixed powder is centrifugally sprayed to prepare small balls;
[0010] (2) mixing the prepared small balls with aluminum powder, boron oxide powder, and carbon powder, and pressing them into a preform;
[0011] (3) melting the master alloy A to above 1000° C., adding the preheated preform, stirring to complete the reaction, adding a covering agent at 900-1100° C. and keeping the temperature for 10-60 min, lowering the temperature to 850° C., adding the master alloy B and keeping the temperature for 5-10 min and stirring to obtain a mixed melt;
[0012] (4) degassing and removing impurities from the mixed melt, refining and deslagging, and then casting to obtain a TiB2 / TiC reinforced high-silicon heat-resistant aluminum-based composite material;
[0013] The master alloy A and master alloy B are raw materials for the aluminum alloy matrix; the master alloy A includes aluminum silicon alloy, aluminum copper alloy, aluminum nickel alloy, aluminum titanium alloy, aluminum manganese alloy and pure aluminum; the master alloy B includes aluminum magnesium alloy and aluminum zinc alloy;
[0014] The metal oxide is copper oxide, chromium oxide, manganese oxide, iron oxide or nickel oxide; the metal powder is nickel powder or copper powder. In the present invention, aluminum powder, titanium powder and metal oxide powder are prepared into small balls and mixed with aluminum powder, boron oxide powder and carbon powder to ensure the staged occurrence of the reaction. In the first stage, aluminum powder, boron oxide powder and carbon powder react to prepare B4C, and then the second stage reaction is carried out. B4C reacts with titanium powder and Al to obtain reinforcing phases TiC and TiB2. The staged occurrence of the reinforcing phase reaction of the present invention can promote the generation and dispersion of ceramic particles, and the generation of TiC / TiB2 ceramic particles is more stable, which is conducive to enhancing the bonding force between TiC / TiB2 ceramic particles and the metal substrate interface. In addition, the use of boron oxide instead of other borides greatly saves costs. Finally, the metal oxide powder reacts with aluminum to release more heat, which can not only speed up the reaction, but also reduce the generation of harmful intermediate phases in the reaction process, promote the generation of ceramic particles TiC and TiB2, and also promote the bonding force between TiC / TiB2 ceramic particles and aluminum substrates.
[0015] More preferably, in step (1), the preform also contains cerium oxide, and the mass of cerium oxide is 5-10% of the mass of the preform. Cerium oxide powder promotes the dispersion of TiC and TiB2 ceramic particles during the reaction process, refines eutectic silicon and intermetallic compounds, promotes the growth of generated TiC particles, improves the generation of the second phase Ti3SiC2 in the composite material, improves the structure of the composite material, and improves the tensile strength, elongation, elastic modulus, thermal expansion coefficient and other properties of the material.
[0016] As a preferred embodiment of the present invention, the average particle size of the aluminum powder, titanium powder, metal oxide and metal powder is 1-10 μm.
[0017] As a preferred embodiment of the present invention, in the step (1), the molar ratio of aluminum powder, titanium powder and metal oxide powder is (1-3): (4-6): (2-4); in the step (2), the molar ratio of aluminum powder, boron oxide powder and carbon powder is (4-8): (1-3): (1-3); the total mass ratio of aluminum powder, boron oxide powder and carbon powder to the mass of the balls is (2-4): (1-2).
[0018] The amount of metal oxide powder added to the pellets also has a great influence on the mechanical properties of the material. Too much metal oxide will lead to the formation of intermediate products in the material structure, reducing the material's tensile strength, elongation, elastic modulus, thermal expansion coefficient and other properties; too little metal oxide will reduce the amount of reinforcement phase generated, and the bonding force between the reinforcement phase and the substrate will be reduced, which will reduce the performance of the composite material.
[0019] As a preferred embodiment of the present invention, the rotation speed of the high-energy ball mill is 200-400 r / min, the time is 1-10 h, and the pressing pressure is 1-20 MPa.
[0020] As a preferred embodiment of the present invention, the parameters of the centrifugal spray are: the air inlet temperature is 100-250° C., the peristaltic pump is set at 20%-80%, and the atomizer frequency is 50Hz-300Hz.
[0021] As a preferred embodiment of the present invention, the diameter of the small ball is 20-50μm. The size of the small ball plays a very important role in the reaction process of the present invention. When the small ball size is larger, its surface area is larger, and the boron carbide particles generated by the first stage reaction are unevenly distributed on the surface of the small ball, affecting the reaction in the second stage, reducing the formation of TiC / TiB2 ceramic particles, promoting the formation of the second phase, and seriously reducing the bonding strength between the ceramic particles and the metal matrix interface, thereby reducing the material performance.
[0022] As a preferred embodiment of the present invention, the aluminum alloy matrix includes the following components in mass percentage: Si: 10% to 15%, Cu: 2.5% to 3.5%, Ni: 2% to 5%, Mn: 0% to 0.5%, Ti: 0.1% to 0.5%, 0% <Mg ≤ 1%, 0% <Zn ≤ 0.5%, single impurity: ≤ 0.05%, total impurities: ≤ 0.15% and the balance Al.
[0023] The covering agent described in the present invention is a commonly used covering agent in the art. The covering agent is used for heat preservation to ensure that the preform and the alloy melt react fully, while reducing contact with air to prevent oxidation.
[0024] As a preferred embodiment of the present invention, in the step (3), the temperature of the preheated preform is 20-150°C.
[0025] As a preferred embodiment of the present invention, in the step (3), mechanical and electromagnetic stirring are used after adding the preheated preform to complete the reaction.
[0026] As a preferred embodiment of the present invention, in the step (3), the intermediate alloy B is added and kept warm for 5-10 minutes, and a stirring method of electromagnetic stirring, mechanical stirring and ultrasonic stirring is adopted, and the number of cycles is 1 to 5 times.
[0027] The present invention uniformly disperses the in-situ reacted ceramic particles in the aluminum alloy matrix by cyclically using electromagnetic stirring, mechanical stirring and ultrasonic stirring, effectively solving the huge problems of ceramic particle agglomeration and difficulty in dispersion, greatly improving the mechanical properties of the material and reducing the preparation cost.
[0028] As a preferred embodiment of the present invention, the speed of the mechanical stirring is 300rpm-700rpm, and the time is 1-10min; the power of the ultrasonic stirring is 800w-2800w, and the time is 1-10min; the power of the electromagnetic stirring is 400-1200W, and the time is 1-10min.
[0029] The present invention also claims protection for the TiB2 / TiC reinforced high-silicon heat-resistant aluminum-based composite material prepared by the preparation method of the TiB2 / TiC reinforced high-silicon heat-resistant aluminum-based composite material.
[0030] As a preferred embodiment of the present invention, the ceramic phase of the TiB2 / TiC reinforced high-silicon heat-resistant aluminum-based composite material includes micron-sized TiC particles and nano-sized TiB2 particles; the total mass fraction of micron-sized TiC particles and nano-sized TiB2 particles in the TiB2 / TiC reinforced high-silicon heat-resistant aluminum-based composite material is 1-20%.
[0031] As a preferred embodiment of the present invention, the size of the TiC particles is less than 1.5 microns, and the size of the TiB2 particles is less than 300 nanometers.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] (1) The preparation method of the present invention generates TiB2 / TiC reinforcing phase in situ in the aluminum substrate in two stages, and the micro-nano TiC and TiB2 ceramic particles have strong interface bonding ability with the metal substrate, and the transition interface is free of impurities, which can greatly improve the mechanical properties of the material. In addition, the ceramic particles produced by the preparation method have a good degree of dispersion in the matrix and less agglomeration. Compared with the fluoride salt method for preparing composite materials, it has a faster reaction process, a fast particle generation speed, and does not produce harmful gases, and has no impact on the environment.
[0034] (2) The preparation method of the present invention can obtain a TiB2 / TiC multiphase reinforced high-silicon heat-resistant aluminum-based composite material. Due to the mixing effect and size effect between different reinforcement particles, it has high strength, high wear resistance, high plasticity and toughness and casting performance. At the same time, adding different metal oxides and rare earth oxide powders to the system of the present invention greatly promotes the dispersion effect of the generated ceramic particles, reduces the generation of intermediate phases, and accelerates the generation of ceramic particles. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 SEM image of the TiB2 / TiC multiphase reinforced high-silicon heat-resistant aluminum-based composite material prepared in Example 4 of the present invention.
[0036] Figure 2 SEM image of the TiB2 / TiC multiphase reinforced high-silicon heat-resistant aluminum-based composite material prepared in Comparative Example 1 of the present invention.
[0037] Figure 3 SEM image of the TiB2 / TiC multiphase reinforced high-silicon heat-resistant aluminum-based composite material prepared in Comparative Example 3 of the present invention.
[0038] Figure 4 SEM image of the TiB2 / TiC multiphase reinforced high-silicon heat-resistant aluminum-based composite material prepared in Comparative Example 4 of the present invention.
[0039] Figure 5 A high-magnification TEM image of the TiB2 / TiC multiphase reinforced high-silicon heat-resistant aluminum-based composite material prepared in Example 4 of the present invention. DETAILED DESCRIPTION
[0040] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0041] Example 1
[0042] A method for preparing a TiB2 / TiC reinforced high-silicon heat-resistant aluminum-based composite material comprises the following steps:
[0043] (1) Aluminum powder, titanium powder, and chromium oxide powder of 1 micron in size were mixed evenly, and after high-energy ball milling for 2 hours at a speed of 300 r / min, the mixed powder was prepared into 30 μm small balls in a centrifugal spray dryer. The molar ratio of aluminum powder, titanium powder, and metal oxide powder in the small balls was 2:4:3; the parameters of centrifugal spraying were: air inlet temperature of 150°C, peristaltic pump setting of 50%, and atomizer frequency of 200 Hz.
[0044] (2) The prepared small balls are mixed with aluminum powder, boron oxide powder and carbon powder so that the small balls are evenly distributed in the powder, and pressed into a cylindrical preform with a diameter of 28 mm and a height of 15 mm under a pressure of 10 MPa; the molar ratio of aluminum powder, boron oxide powder and carbon powder is 6:2:1, and the mass ratio of the small balls to the mixed powder of (aluminum powder + boron oxide powder + carbon powder) is 1:2.
[0045] (3) The intermediate alloy A was melted to above 1000°C, 500 g of the preheated preform was added, and the preform was fully reacted in the high-temperature melt. A covering agent was added at 1100°C and kept warm for 40 min. The temperature was lowered to 850°C, and the intermediate alloy B was added and kept warm for 10 min. Then, mechanical stirring was used for 3 min at a speed of 300 rpm, ultrasonic stirring was used for 3 min at a power of 800 W, and electromagnetic stirring was used for 3 min at a power of 400 W for 5 cycles to obtain a mixed melt.
[0046] (4) The mixed melt is degassed and impurity-removed, refined and slag-removed, and then cast to obtain a TiB2 / TiC reinforced high-silicon heat-resistant aluminum-based composite material with a mass fraction of 10%.
[0047] Master alloy A and master alloy B are raw materials for aluminum alloy matrix; master alloy A is composed of aluminum silicon alloy, aluminum copper alloy, aluminum nickel alloy, aluminum titanium alloy, aluminum manganese alloy and pure aluminum; master alloy B is composed of aluminum magnesium alloy and aluminum zinc alloy. The aluminum alloy matrix includes the following components in mass percentage: Si: 13%, Cu: 3%, Ni: 2.5%, Mn: 0.25%, Ti: 0.3%, Mg: 1%, Zn: 0.3%, single impurity: ≤0.05%, total impurity: ≤0.15% and the balance Al.
[0048] Example 2
[0049] A method for preparing a TiB2 / TiC reinforced high-silicon heat-resistant aluminum-based composite material comprises the following steps:
[0050] (1) Aluminum powder, titanium powder, and metal nickel powder of 5 microns in size were mixed evenly, and after high-energy ball milling for 1 hour at a speed of 200 r / min, the mixed powder was prepared into 20 μm small balls in a centrifugal spray dryer. The molar ratio of aluminum powder, titanium powder, and metal chromium oxide powder in the small balls was 1:6:2; the parameters of centrifugal spraying were: air inlet temperature of 100°C, peristaltic pump setting of 80%, and atomizer frequency of 300 Hz.
[0051] (2) The prepared small balls are mixed with aluminum powder, boron oxide powder and carbon powder so that the small balls are evenly distributed in the powder, and pressed into a cylindrical preform with a diameter of 28 mm and a height of 15 mm under a pressure of 20 MPa; the molar ratio of aluminum powder, boron oxide powder and carbon powder is 4:1:3, and the mass ratio of the small balls to the mixed powder of (aluminum powder + boron oxide powder + carbon powder) is 1:2.
[0052] (3) The intermediate alloy A is melted to above 1000°C, 200 g of the preheated preform is added, and a sufficient reaction occurs inside the preform in the high-temperature melt. A covering agent is added and kept warm for 50 min at 1000°C, the temperature is lowered to 850°C, the intermediate alloy B is added and kept warm for 10 min, and then mechanical stirring is used for 5 min at a speed of 300 rpm, ultrasonic stirring is used for 5 min at a power of 800 W, and electromagnetic stirring is used for 5 min at a power of 400 W for 5 cycles to obtain a mixed melt.
[0053] (4) The mixed melt is degassed and impurity-removed, refined and slag-removed, and then cast to obtain a TiB2 / TiC reinforced high-silicon heat-resistant aluminum-based composite material with a mass fraction of 10%.
[0054] Master alloy A and master alloy B are raw materials for aluminum alloy matrix; master alloy A is composed of aluminum silicon alloy, aluminum copper alloy, aluminum nickel alloy, aluminum titanium alloy, aluminum manganese alloy and pure aluminum; master alloy B is composed of aluminum magnesium alloy and aluminum zinc alloy. The aluminum alloy matrix includes the following components in mass percentage: Si: 15%, Cu: 3.5%, Ni: 2%, Mn: 0.5%, Ti: 0.1%, Mg: 0.5%, Zn: 0.5%, single impurity: ≤0.05%, total impurity: ≤0.15% and the balance of Al.
[0055] Example 3
[0056] A method for preparing a TiB2 / TiC reinforced high-silicon heat-resistant aluminum-based composite material comprises the following steps:
[0057] (1) Aluminum powder, titanium powder, and chromium oxide powders of 10 micrometers in size were mixed evenly, and after high-energy ball milling for 2 hours at a speed of 300 r / min, the mixed powder was prepared into 50 μm small balls in a centrifugal spray dryer. The molar ratio of aluminum powder, titanium powder, and metal chromium oxide powder in the small balls was 2:4:4; the parameters of centrifugal spraying were: air inlet temperature of 100°C, peristaltic pump setting of 20%, and atomizer frequency of 50 Hz.
[0058] (2) The prepared small balls were mixed with aluminum powder, boron oxide powder and carbon powder so that the small balls were evenly distributed in the powder, and pressed into a cylindrical preform with a diameter of 28 mm and a height of 15 mm under a pressure of 1 MPa; the molar ratio of aluminum powder, boron oxide powder and carbon powder was 8:3:1, and the mass ratio of the small balls to the mixed powder of (aluminum powder + boron oxide powder + carbon powder) was 1:4.
[0059] (3) The intermediate alloy A is melted to above 1000°C, 200 g of the preheated preform is added, and the preform is fully reacted in the high-temperature melt. A covering agent is added at 1000°C and the temperature is kept at 850°C for 10 min. The temperature is then lowered to 850°C, and the intermediate alloy B is added and kept at 10 min. Then, mechanical stirring is performed for 10 min at a speed of 300 rpm, ultrasonic stirring is performed for 10 min at a power of 800 W, and electromagnetic stirring is performed for 10 min at a power of 400 W. The mixed melt is obtained by repeating the cycle 5 times.
[0060] (4) The mixed melt is degassed and impurity-removed, refined and slag-removed, and then cast to obtain a TiB2 / TiC reinforced high-silicon heat-resistant aluminum-based composite material with a mass fraction of 10%.
[0061] Master alloy A and master alloy B are raw materials for aluminum alloy matrix; master alloy A is composed of aluminum silicon alloy, aluminum copper alloy, aluminum nickel alloy, aluminum titanium alloy, aluminum manganese alloy and pure aluminum; master alloy B is composed of aluminum magnesium alloy and aluminum zinc alloy. The aluminum alloy matrix includes the following components in mass percentage: Si: 13%, Cu: 3%, Ni: 2.5%, Mn: 0.25%, Ti: 0.3%, Mg: 1%, Zn: 0.3%, single impurity: ≤0.05%, total impurity: ≤0.15% and the balance Al.
[0062] Example 4
[0063] A method for preparing a TiB2 / TiC reinforced high-silicon heat-resistant aluminum-based composite material comprises the following steps:
[0064] (1) Aluminum powder, titanium powder, and metal chromium oxide powders of 5 micrometers in size were mixed evenly, and after high-energy ball milling for 10 hours at a speed of 200 r / min, the mixed powder was prepared into 30 μm small balls in a centrifugal spray dryer. The molar ratio of aluminum powder, titanium powder, and metal chromium oxide powder in the small balls was 2:4:3; the parameters of centrifugal spraying were: air inlet temperature of 180°C, peristaltic pump setting of 60%, and atomizer frequency of 200 Hz.
[0065] (2) The prepared small balls are mixed with aluminum powder, boron oxide powder and carbon powder so that the small balls are evenly distributed in the powder, and rare earth cerium oxide powder with a mass fraction of 5% of the preform is added. After sufficient mixing, the preform is pressed into a cylindrical preform with a diameter of 28 mm and a height of 15 mm under a pressure of 12 MPa; the molar ratio of aluminum powder, boron oxide powder and carbon powder is 6:2:1, and the mass ratio of the small balls to the mixed powder of (aluminum powder + boron oxide powder + carbon powder) is 1:2.
[0066] (3) The intermediate alloy A is melted to above 1000°C, 200 g of the preheated preform is added, and the preform is fully reacted in the high-temperature melt. A covering agent is added at 1000°C and the temperature is kept at 850°C for 10 min. The temperature is then reduced to 850°C, and the intermediate alloy B is added and kept at 10 min. Then, mechanical stirring is performed for 5 min at a speed of 600 rpm, ultrasonic stirring is performed for 5 min at a power of 1000 W, and electromagnetic stirring is performed for 5 min at a power of 800 W. The mixed melt is obtained by repeating the cycle 5 times.
[0067] (4) The mixed melt is degassed and impurity-removed, refined and slag-removed, and then cast to obtain a TiB2 / TiC reinforced high-silicon heat-resistant aluminum-based composite material with a mass fraction of 10%.
[0068] Master alloy A and master alloy B are raw materials for aluminum alloy matrix; master alloy A is composed of aluminum silicon alloy, aluminum copper alloy, aluminum nickel alloy, aluminum titanium alloy, aluminum manganese alloy and pure aluminum; master alloy B is composed of aluminum magnesium alloy and aluminum zinc alloy. The aluminum alloy matrix includes the following components in mass percentage: Si: 13%, Cu: 3%, Ni: 2.5%, Mn: 0.25%, Ti: 0.3%, Mg: 1%, Zn: 0.3%, single impurity: ≤0.05%, total impurity: ≤0.15% and the balance Al.
[0069] Example 5
[0070] The only difference between the preparation method of a TiB2 / TiC multiphase reinforced high-silicon heat-resistant aluminum-based composite material and Example 3 is that in step (3), the number of cycles of electromagnetic stirring, ultrasonic stirring, and mechanical stirring is 2.
[0071] Comparative Example 1
[0072] The only difference between the preparation method of a TiB2 / TiC multiphase reinforced high-silicon heat-resistant aluminum-based composite material and Example 4 is that in step (1), the molar ratio of aluminum powder, titanium powder and metal oxide powder in the small ball is 2:4:1.
[0073] Comparative Example 2
[0074] The only difference between the method for preparing a TiB2 / TiC multiphase reinforced high-silicon heat-resistant aluminum-based composite material and that in Example 4 is that in step (1), the particle size of the small balls is 60 μm.
[0075] Comparative Example 3
[0076] The only difference between the method for preparing a TiB2 / TiC multiphase reinforced high-silicon heat-resistant aluminum-based composite material and that in Example 4 is that in the step (1), the particle size of the small balls is 90 μm.
[0077] Comparative Example 4
[0078] A method for preparing a TiB2 / TiC reinforced high-silicon heat-resistant aluminum-based composite material comprises the following steps:
[0079] (1) Aluminum powder, titanium powder, chromium oxide powder, boron oxide powder and carbon powder, all of which are 1 micron in size, are mixed and subjected to high-energy ball milling at a rotation speed of 300 r / min for 2 hours in alternating forward and reverse directions. The mixed powder is then pressed into a cylindrical preform with a diameter of 28 mm and a height of 15 mm. The molar ratio of aluminum powder, titanium powder, chromium oxide, boron oxide powder and carbon powder is 14:4:3:4:1.
[0080] (2) The intermediate alloy A is melted to above 1000°C, 500 g of the preheated preform is added, and the preform is fully reacted in the high-temperature melt. A covering agent is added at 1100°C and kept warm for 40 min. The temperature is lowered to 900°C, and the intermediate alloy B is added and kept warm for 10 min. Then, mechanical stirring is used for 3 min at a speed of 300 rpm, ultrasonic stirring is used for 3 min at a power of 800 W, and electromagnetic stirring is used for 3 min at a power of 400 W to obtain a mixed melt.
[0081] (3) The mixed melt is degassed and de-impurified, refined and slag-removed, and then cast to obtain a TiB2 / TiC reinforced high-silicon heat-resistant aluminum-based composite material with a mass fraction of 10%.
[0082] Master alloy A and master alloy B are raw materials for aluminum alloy matrix; master alloy A is composed of aluminum silicon alloy, aluminum copper alloy, aluminum nickel alloy, aluminum titanium alloy, aluminum manganese alloy and pure aluminum; master alloy B is composed of aluminum magnesium alloy and aluminum zinc alloy. The aluminum alloy matrix includes the following components in mass percentage: Si: 13%, Cu: 3%, Ni: 2.5%, Mn: 0.25%, Ti: 0.3%, Mg: 1%, Zn: 0.3%, single impurity: ≤0.05%, total impurity: ≤0.15% and the balance Al.
[0083] Table 1
[0084]
[0085] According to the results in Table 1, by comparing Example 1 and Comparative Example 1, it can be seen that the reduction in the oxide content leads to incomplete reaction, the appearance of a second phase, and agglomeration of ceramic particles. Figure 2 It can be seen that a second phase is generated in Comparative Example 1. By comparing Example 1 and Comparative Examples 2-3, it can be seen that as the diameter of the small ball increases, its performance first increases and then gradually decreases. Figure 1 It can be seen that no second phase is generated in Example 4, but Figure 3 It can be seen that a rod-like second phase is generated in Comparative Example 3.
[0086] By comparing Example 4 and Comparative Example 4, it can be seen that the method without preparing the small balls cannot react smoothly to generate ceramic particles. Figure 4 As shown, a large number of intermediate rod-like phases are generated, which seriously affects the mechanical properties of the composite material. The method of the present invention can make the reaction proceed in stages, without generating intermediate phases, and directly synthesize ceramic particles, such as Figure 5 As shown, the generated TiC particles are spherical, while the TiB2 particles are hexagonal and long strips.
[0087] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a TiB2 / TiC reinforced high-silicon heat-resistant aluminum-based composite material, characterized in that: The steps include: (1) Aluminum powder, titanium powder and metal oxide or metal powder are mixed by high-energy ball milling, and the mixed powder is centrifugally sprayed to prepare small balls; (2) mixing the prepared small balls with aluminum powder, boron oxide powder, and carbon powder, and pressing them into a preform; (3) melting the master alloy A to above 1000° C., adding the preheated preform, stirring to complete the reaction, adding a covering agent at 900-1100° C. and keeping the temperature for 10-60 min, lowering the temperature to 850° C., adding the master alloy B and keeping the temperature for 5-10 min and stirring to obtain a mixed melt; (4) degassing and removing impurities from the mixed melt, refining and deslagging, and then casting to obtain a TiB2 / TiC reinforced high-silicon heat-resistant aluminum-based composite material; The master alloy A and master alloy B are raw materials for the aluminum alloy matrix; the master alloy A includes aluminum silicon alloy, aluminum copper alloy, aluminum nickel alloy, aluminum titanium alloy, aluminum manganese alloy and pure aluminum; the master alloy B includes aluminum magnesium alloy and aluminum zinc alloy; The metal oxide is copper oxide, chromium oxide, manganese oxide, iron oxide or nickel oxide; the metal powder is nickel powder or copper powder.
2. The method for preparing the TiB2 / TiC reinforced high silicon heat-resistant aluminum-based composite material according to claim 1, characterized in that: In the step (1), the preform further contains cerium oxide, and the mass of the cerium oxide is 5-10% of the mass of the preform.
3. The method for preparing the TiB2 / TiC reinforced high silicon heat-resistant aluminum-based composite material according to claim 1, characterized in that: In the step (1), the molar ratio of aluminum powder, titanium powder and metal oxide powder is (1-3): (4-6): (2-4); in the step (2), the molar ratio of aluminum powder, boron oxide powder and carbon powder is (4-8): (1-3): (1-3); the total mass ratio of aluminum powder, boron oxide powder and carbon powder to the mass of the balls is (2-4): (1-2).
4. The method for preparing the TiB2 / TiC reinforced high silicon heat-resistant aluminum-based composite material according to claim 1, characterized in that: The rotation speed of the high energy ball mill is 200-400 r / min, the time is 1-10 h; the pressing pressure is 1-20 MPa.
5. The method for preparing the TiB2 / TiC reinforced high silicon heat-resistant aluminum-based composite material according to claim 1, characterized in that: The parameters of the centrifugal spray are: air inlet temperature is 100-250° C., peristaltic pump is set at 20%-80%, and atomizer frequency is 50 Hz-300 Hz.
6. The method for preparing the TiB2 / TiC reinforced high silicon heat-resistant aluminum-based composite material according to claim 1, characterized in that: The diameter of the small ball is 20-50 μm; the average particle diameters of the aluminum powder, titanium powder, metal oxide and metal powder in the small ball are all 1-10 μm.
7. The method for preparing the TiB2 / TiC reinforced high silicon heat-resistant aluminum-based composite material according to claim 1, characterized in that: The aluminum alloy matrix includes the following components in mass percentage: Si: 10% to 15%, Cu: 2.5% to 3.5%, Ni: 2% to 5%, Mn: 0% to 0.5%, Ti: 0.1% to 0.5%, 0% <Mg ≤ 1%, 0% <Zn ≤ 0.5%, single impurity: ≤ 0.05%, total impurities: ≤ 0.15% and the balance Al.
8. The method for preparing the TiB2 / TiC reinforced high silicon heat-resistant aluminum-based composite material according to claim 1, characterized in that: In the step (3), the intermediate alloy B is added and kept warm for 5-10 minutes, and a stirring method of electromagnetic stirring, mechanical stirring and ultrasonic stirring is adopted, and the number of cycles is 1 to 5 times.
9. The TiB2 / TiC reinforced high silicon heat-resistant aluminum-based composite material prepared by the method for preparing the TiB2 / TiC reinforced high silicon heat-resistant aluminum-based composite material according to any one of claims 1 to 8, characterized in that: It comprises micron-sized TiC particles and nano-sized TiB2 particles; the total mass fraction of the micron-sized TiC particles and nano-sized TiB2 particles in the TiB2 / TiC reinforced high-silicon heat-resistant aluminum-based composite material is 1-20%.
10. The ceramic phase of the TiB2 / TiC reinforced high silicon heat resistant aluminum based composite material as claimed in claim 9, characterized in that: The size of the TiC particles is less than 1.5 micrometers, and the size of the TiB2 particles is less than 300 nanometers.
Citation Information
Patent Citations
Preparation method of in-situ Al2O3 particle reinforced aluminum-based composite material
CN115418520A
A high performance aluminum-based composite material and preparation method thereof
CN116144997B
Preparation method of in-situ dual-phase nanoparticle reinforced aluminum matrix composite
CN116607041A
Cited By
Alloy composite material for automobile armrest, preparation process and automobile armrest
CN120158650A
Manufacturing method of high-toughness composite aluminum alloy hub
CN121976081A
A manufacturing method of a high-toughness composite aluminum alloy wheel hub
CN121976081B